2016
DOI: 10.15193/zntj/2016/106/131
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition of phenolic compounds and tocopherols in broccoli heads during short-term storage

Abstract: S u m m a r yBroccoli (Brassica oleracea L. var. italica) contains numerous biologically active compounds. However, their levels change during processing and storage.The objective of the research study was to determine the effect of short-term storage (1 ÷ 4 days) of broccoli heads at different temperatures (3 ºC, 16 ºC, and 21 ºC) on the contents of phenolic acids, selected flavonoids (quercetin and kaempferol), and tocopherols. Broccoli heads were harvested in autumn when they reached their maximum size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
0
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
4
0
0
Order By: Relevance
“…In the present study, the concentration of kaempferol in broccoli heads was 3-4 times higher than that of quercetin. This is consistent with the results of the research conducted by Gliszczyńska-Świgło et al (2007), Kałużewicz et al (2016) and Koh et al (2009). In contrast, Bahorun et al (2004) observed that the concentration of quercetin was 5 times higher than that of kaempferol.…”
Section: Resultssupporting
confidence: 91%
“…In the present study, the concentration of kaempferol in broccoli heads was 3-4 times higher than that of quercetin. This is consistent with the results of the research conducted by Gliszczyńska-Świgło et al (2007), Kałużewicz et al (2016) and Koh et al (2009). In contrast, Bahorun et al (2004) observed that the concentration of quercetin was 5 times higher than that of kaempferol.…”
Section: Resultssupporting
confidence: 91%
“…The total phenolic content and the amounts of ferulic, sinapic and caffeic acids increased along with the duration of storage both in the plants treated with the biostimulants and in the control plants. This is consistent with the results of our previous studies (Kałużewicz et al, 2016), where the total phenolic content increased by more than 180% after three days of storage, whereas the content of caffeic, ferulic and sinapic acids grew by 60%, 198% and 151%, respectively. Leja et al (2001) and Starzyńska et al (2003) observed the same trend in broccoli heads stored at room temperature.…”
Section: Resultssupporting
confidence: 93%
“…However, this trend was not observed in the first year of the experiment, when the content of quercetin after three days of storage was the same as in the fresh heads, while the content of kaempferol decreased. The increase in the contents of quercetin and kempferol during storage in the second year is consistent with the results of another study by Kałużewicz et al (2016). The researchers observed that after three days of storage at a temperature of 21°C the amount of quercetin increased by 56%, while the content of kempferol grew by 27%.…”
supporting
confidence: 89%
“…In this study the decrease in total polyphenols was continuing by the second month of research; next the level of these constituents increased substantially to be continued at high level, near the level in the blanched material, until the end of a study period. An increase in the level of these constituents to the value even exceeding the initial value has also been confirmed by Kaluzewicz et al [49] and Kim et al [50]; however, an increase noted in this research did not exceeded the level determined in the fresh vegetable. As Hakkinen and Torronen [51] claim, throughout several months of storage of strawberries, both an increase and a decrease in total polyphenols were possible.…”
Section: Total Polyphenolssupporting
confidence: 81%